A study of casting high‐boron high‐speed steel roll materials. Issue 10 (October 2015) - Li, X.; Hou, J.; Qu, Y.; Fu, H.
<x xml:space="preserve">Abstract</x> In this paper, we design and prepare five kinds of high‐boron high‐speed steel roll materials. The microstructure, mechanical property and wear resistance of high‐boron high‐speed steel roll materials were studied by means of optical microscopy (OM), scanning electron microscopy (SEM), X‐ray diffraction (XRD) and hardness measurement, impact test and abrasion test. The results show that as‐cast microstructure of high‐boron high‐speed steel consists of martensite, retained austenite and borocarbide. Hardness of as‐cast high‐boron high‐speed steel excels 64 HRC. In unmodified high‐boron high‐speed steel, eutectic borocarbide is distributed in a network along the grain boundary. With the addition of RE‐Mg‐Ti compound modifier, the networks of borocarbide is broken. The hardness of high‐boron high‐speed steel gradually decreased with the increase of tempering temperature. Under the same conditions, the impact toughness of unmodified high‐boron high‐speed steel roll material is slightly lower than that of modified steel. The wear resistance of modified high‐boron high‐speed steel roll material is greater than that of high‐carbon high‐vanadium high‐speed steel roll.